Nematode (Roundworm) Infections in Fish - Roy P. Yanong (EDIS)
This document is Circular 91, one of a series from the Department of Fisheries and Aquatic Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: December 2002.